1989
DOI: 10.1620/tjem.157.193
|View full text |Cite
|
Sign up to set email alerts
|

A role of the cancer cell membrane fluidity in the cancer metastases: An ESR study.

Abstract: AH66F or Yoshida sarcoma (YS) cells were transplanted intraperitoneally into male Donryu rats. Cancer cells obtained from ascites were suspended in saline solution (10' cells ml) after washing. Then, 0.1 ml of each suspension obtained from both strains was injected into the tail vein of 5 rats, respectively. Each metastatic nodule, 1 mm or less in a diameter, thus obtained was then injected into the peritoneal cavity in which these metastatic cells come to free. After 10 days, cancer cells obtained from each a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 9 publications
1
53
1
Order By: Relevance
“…Even though no univocal trend is evident regarding the direction of alterations in tumor cell membrane fluidity [54], in most tumors malignant cell membranes have been found to possess higher fluidity than those of their healthy counterparts. It has also been shown that such structural change significantly correlates with an increased migratory/invasive aptitude and malignant potential of tumor cells as well as with a poor prognosis [52], [53], [55], [56]. Therefore, in the present study, two-photon microscopy imaging of cells labelled with the membrane fluorescent probe Laurdan was used to investigate whether fluidity changes in plasma membranes could occur as a result of tumor cell/fibroblast co-culturing.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Even though no univocal trend is evident regarding the direction of alterations in tumor cell membrane fluidity [54], in most tumors malignant cell membranes have been found to possess higher fluidity than those of their healthy counterparts. It has also been shown that such structural change significantly correlates with an increased migratory/invasive aptitude and malignant potential of tumor cells as well as with a poor prognosis [52], [53], [55], [56]. Therefore, in the present study, two-photon microscopy imaging of cells labelled with the membrane fluorescent probe Laurdan was used to investigate whether fluidity changes in plasma membranes could occur as a result of tumor cell/fibroblast co-culturing.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in the motional freedom of lipids and protein molecules in the cellular membrane represent a critical feature of pathological cells, influencing several aspects of their behaviour such as the response to chemotherapeutic agents [48], [49], availability or activation of membrane receptors [50], [51], migratory, invasive and/or metastatic potential [52], [53]. Even though no univocal trend is evident regarding the direction of alterations in tumor cell membrane fluidity [54], in most tumors malignant cell membranes have been found to possess higher fluidity than those of their healthy counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, alterations in membrane fluidity in cancer cells may be correlated with their malignant potential [30,32] and capability to metastasize [33]. Although no pattern has been described, such alterations can be responsible for cancer cell sensitivity or resistance to several anticancer drugs [31].…”
Section: Features Of Cancer Cell Membranesmentioning
confidence: 99%
“…Plasma membrane fluidity depends on the composition of the lipids and proteins in the membrane, and has been demonstrated to be significantly associated with the malignant potential of cancer cells (28), with alterations in the plasma membrane fluidity of cancer cells associated with their capacity to form metastases (29). In lung cancer, studies reported that patients with high plasma membrane fluidity had poorer prognoses than those with less fluid membranes, and the fluidity variable may be used as an independent additional prognostic factor (28,30,31).…”
Section: Discussionmentioning
confidence: 99%